If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 2)(8y + -7) = 0 Reorder the terms: (2 + 7x)(8y + -7) = 0 Reorder the terms: (2 + 7x)(-7 + 8y) = 0 Multiply (2 + 7x) * (-7 + 8y) (2(-7 + 8y) + 7x * (-7 + 8y)) = 0 ((-7 * 2 + 8y * 2) + 7x * (-7 + 8y)) = 0 ((-14 + 16y) + 7x * (-7 + 8y)) = 0 (-14 + 16y + (-7 * 7x + 8y * 7x)) = 0 (-14 + 16y + (-49x + 56xy)) = 0 Reorder the terms: (-14 + -49x + 56xy + 16y) = 0 (-14 + -49x + 56xy + 16y) = 0 Solving -14 + -49x + 56xy + 16y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + -49x + 56xy + 14 + 16y = 0 + 14 Reorder the terms: -14 + 14 + -49x + 56xy + 16y = 0 + 14 Combine like terms: -14 + 14 = 0 0 + -49x + 56xy + 16y = 0 + 14 -49x + 56xy + 16y = 0 + 14 Combine like terms: 0 + 14 = 14 -49x + 56xy + 16y = 14 Add '-16y' to each side of the equation. -49x + 56xy + 16y + -16y = 14 + -16y Combine like terms: 16y + -16y = 0 -49x + 56xy + 0 = 14 + -16y -49x + 56xy = 14 + -16y Reorder the terms: -14 + -49x + 56xy + 16y = 14 + -16y + -14 + 16y Reorder the terms: -14 + -49x + 56xy + 16y = 14 + -14 + -16y + 16y Combine like terms: 14 + -14 = 0 -14 + -49x + 56xy + 16y = 0 + -16y + 16y -14 + -49x + 56xy + 16y = -16y + 16y Combine like terms: -16y + 16y = 0 -14 + -49x + 56xy + 16y = 0 The solution to this equation could not be determined.
| =(7x+2)(8y-7) | | -2(x^2+1)=0 | | 18=-3(n-4) | | 4x^2+2.4x+0.36=9.7 | | 3x-1+x=4x+2 | | -5(6r+3)=-15 | | 4x^2+120x+3600=9700 | | 3x^2+16=-26 | | F(x)=19x^5-4x^4-1 | | -2(-3)+y=4 | | 0=19x^5-4x^4-1 | | 11+4n-8n=n+1 | | 5x^2-7=9 | | -2(1)+y=4 | | 1/3(x-9)= | | 6n-20=16 | | 7h+16=2 | | -2(2f+4)=4 | | -2x+11-5x-7=-10 | | 3(2x-5)-x=3+6x | | log(9)(2x-7)=2 | | 2/6-2x/-1=7 | | 8=4x-3+7x | | 6t+30=0 | | x=10000/23*0.25*20+10000-2000 | | 3x^2=56x | | 12-4d=20 | | x+15+3x-10=25 | | h+2x-12=-36 | | 3x+8-3(3x-2)=4(x-1) | | 7+4b=3 | | y=-1E-06x+0.8575 |